Transforming smart cities with social innovation: Penta helix multi-stakeholders framework - Calzada, I (Regional Studies Association, 2017)
The EU Framework Programme Horizon 2020 (H2020), under its Smart City and Communities (SCC) scheme, encourages European cities and regions to activate their given social and economic structures. Although, it goes without saying that the transformation of smart cities seems to be rather difficult as long as socially innovative restructurating does not take place among stakeholders. Based on a current H2020 SCC project, this paper sheds some light on the theoretical contributions of the triple and quadruple multi-stakeholder helix approaches. As such, it advocates that social innovation could rarely entirely flourish among stakeholders simply because the stakeholders’ structures show a fixed interdependence, far enough to contribute to a real transformation based on experimental governance and the urban commons. Hence, this paper will present the Penta Helix multi-stakeholder framework referring to the transformative alliance between the public sector; the private sector; the academia, science, and technology sector; and the civic society. Ultimately, especially the novel approach of this paper will be to include the fifth helix: social entrepreneurs, activists, bricoleurs, brokers, and/or assemblers. This paper will attempt to define and locate the profile of this fifth helix as the key element to activating a real socially innovative transformation in smart cities’ understanding and practices. This paper will be based on ongoing fieldwork research by presenting conclusions from some European cities and regions. Within the realm of this paper, social innovation could be presented as a methodological policy tool that could make effective systemic transformations in smart city institutional projects.